Trial of ORG 10172 in acute stroke treatment classification and associated risk factors of ischemic stroke: a prospective study from a tertiary care center in South India - Manorenj, Sandhya; Inturi, Snehalatha; B., Jyotsna (International Journal of Research in Medical Sciences, 2016)
Background: Stroke is the leading cause of acquired disability worldwide. Better understanding of risk factors helps to reduce the community burden of stroke. Aim of the study was to determine pattern of ischemic stroke subtype and associated risk factors. Methods: Of 220 patients with first ever stroke, 168 patients of ischemic stroke were enrolled prospectively from January 2016 to May 2016 at ESIC Superspeciality hospital, Hyderabad. Patients were categorized in accordance with the Trial of Org 10172 in Acute Stroke treatment (TOAST) criteria. Results: Of 168 patients, 110 (65.4%) were males; male to female ratio was 1.8:1. The mean age was 53.912.3 years. Small vessel occlusion (SVO) occurred in younger age group as compared to other stroke subtypes. Frequency of large-artery atherosclerosis (LAA) (46.4%) was highest (Extracranial: 41.1%, intracranial: 36.9%), followed by SVO (32.4%), cardio embolism (15.4%), undetermined (4.7%) and other determined causes (1.1%). Risk factors included dyslipidemia (79%), hypertension (67.8%), smoking (58.3%), alcohol use (54.7%), diabetes (40.4%) and physical inactivity (27.3%). Common association observed was smoking (P - 0.004) and alcohol (P - 0.003) with LAA and SVO, and dilated cardiomyopathy with cardio embolism. Conclusions: LAA was observed frequently than SVO. Frequency of SVO was lower than Asian but higher than western, while cardio embolism was lower than Western and similar to Asian stroke studies. Dyslipidemia was the predominant risk factor than hypertension reported from Asian and Western stroke registry. This unique pattern can be attributed to differences in demographic and risk factor profiles. The study confirms the need for vigorous primary and secondary prevention measures targeting modifiable risk factors of stroke.